SWOT Analysis of Hospital Health Services in DKT TK IV Hospital Kediri 2019 - Nugraheni, Reny; Kirana, Gerardin Ranind (STRADA : Jurnal Ilmiah Kesehatan, 2021)
SWOT analysis, strategic planning can be done to evaluate strengths, weakness, opportunities, and challenges in an organization. The metode used is the literature study method which is based on the paper as a basic reference in journal preparation. The instruments in the study used interview guidelines and SWOT questionnaires using qualitative analysis and quantita Analysis in the literature analysis of previous paper with IFAS and EFAS approaches. The results of the matrix calculation show that DKT Kediri Hospital located in second Quadrant. Indicates that an organization is strong but faces great challenges. Organization are advised to immediately multiply the variety of tactical strategies. SWOT analysis is expected that an organization here at DKT Kediri Hospital will be able to maximize the strengths and opportunities they have to face challenges in the external environment and minimize the weakness owned by the organization.